DISTANCE EDUCATION: EVOLUTION OF THE NORMATIVE CONTEXT IN ARGENTINA AND OF THE INSTITUTIONAL CONTEXT IN THE NATIONAL UNIVERSITY OF THE SOUTH (Perspectivas de las Ciencias Económicas y Jurídicas, 2020)
The constant changes in society, the advancement of new technologies and the requirement to have people prepared to face this reality, require educational institutions to readjust the training offer, with Distance Education being one of the strategies they use. However, the growth of this modality should be accompanied and encouraged by a regulatory environment at a general level, which is updated periodically. The objective of the present investigation is to describe the evolutive context of Distance Education, both in legislative matters in the Argentine Republic, and at the institutional level within the National University of the South and particularly in the Department of Administration Sciences, mentioning the process of change that is transiting one of the subjects of the career Degree in Administration. After the journey through the regulations, it can be concluded that the changes that were incorporated over the years, although they were gradual respond to the growth of the modality, which has generated the need to adjust the regulations at the national level and, in consequence, within the universities to generate a framework according to what the new demands demand.
Keywords: Distance Education; regulatory context of Argentina; higher education system